The illustrated children's Bible as cultural text in the construction of Afrikaner national identity - Barnard, Louis H. (Stellenbosch : Stellenbosch University, 2008)
Thesis (MPhil(Visual Arts. Illustration))--Stellenbosch University, 2007.